Strategi Digital Branding Pt Semen Padang Dalam Membangun Brand Awareness (Studi Kasus Kualitatif Produk Sepablock Pt Semen Padang) - Viona Agmey Fadilla; Ria Edlina (CV. ITTC INDONESIA, 2026)
The development of digital technology has changed the way companies build their brand image, one of which is through digital branding strategies. This study was motivated by the strategic move of PT Semen Padang to launch an innovative sub-brand product called SEPABLOCK (Semen Padang Bata Interlock). Although PT Semen Padang has a strong reputation for its bagged cement products, this has created a challenge in the form of “single memory” in the community, which can hinder brand awareness of new products with different technical characteristics. This study aims to analyze the digital branding strategies implemented by PT Semen Padang through social media and websites to educate the market and build brand awareness of SEPABLOCK, particularly in the context of the characteristics of the construction market and local culture in West Sumatra. The method used is descriptive qualitative to dissect the digital communication model that integrates aspects of education, product visualization, and messages based on local needs such as cost efficiency and earthquake resistance. The novelty of this research lies in its focus on analyzing sub-brand products in the heavy industry sector (state-owned enterprises) operating in markets with specific socio-cultural characteristics. The results of this study are expected to contribute theoretically to the effectiveness of digital branding in the building materials industry and provide practical recommendations for companies in optimizing digital media to expand the market share of innovative products